Electrochemical Conversion of Bicarbonate to Formate Mediated by the Complex RuIII(edta) (edta4– = ethylenediaminetetraacetate). Issue 34 (28th October 2014) - Chatterjee, Debabrata; Jaiswal, Namita; Banerjee, Priyabrata
Abstract: In this paper, we present the first example of a ruthenium(III) complex, [Ru III (edta)] (edta = ethylenediaminetetraacetate), that catalyzes the electrochemical conversion of hydrogen carbonate to formate selectively. The formation of an [Ru III (edta)(HCO3 )] 2– species through the reaction of the [Ru III (edta)(H2 O)] – catalyst and hydrogen carbonate (HCO3 – ) was studied kinetically by using the stopped‐flow technique. The value of the second‐order rate constant for the formation of the [Ru III (edta)(HCO3 )] 2– complex was 82 ± 7M –1  s –1 at 25 °C and pH = 6.4. Electrochemical reduction of hydrogen carbonate (HCO3 – ) was achieved by carrying out constant‐potential bulk electrolysis at –0.4 V (vs. SCE) with a mercury‐pool cathode at pH = 6.4. The formation of formate as the only reduction product was evidenced by a 13 C NMR analysis of the reaction mixture obtained after electrolysis. Abstract : [Ru III (edta)(H2 O)] – (edta = ethylenediaminetetraacetate) mediates the electrochemical conversion of hydrogen carbonate to formate through the formation of an [Ru III (edta)(HCO3 )] 2– species, which undergoes electrochemical reduction at –0.4 V (vs. SCE) at a mercury‐pool cathode at pH = 6.4. This results in the formation of formate as the only product.